Psychological features of people with borderline personality disorders - Morozova, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article presents the results of an empirical study of the psychological features of people with signs of borderline personality disorder. The study involved 40 people with signs of borderline personality disorder aged 14-56 years. According to the purpose of the study, the following tasks have been set: To investigate personality with borderline disorder; Identify and evaluate the neurotic states of a person with a borderline personality disorder; Conduct correlation analysis to investigate trends in the relationship between the indicator of the number of signs of borderline disorder and personal characteristics. The following research methods were used: 5PFQ Big Five technique (R. McCray, P. Costa), Clinical questionnaire for the detection and evaluation of neurotic conditions (KK Yakhin, DM Mendelevich) and Methods for diagnosing borderline personality disorder (TY Lasovskaya, CP Korolenko, SV Yaechnikov). The data obtained were subjected to a mathematical and statistical analysis procedure using the SPSS Statistic program. It is proved that emotional lability (instability of emotions), impulsiveness and self-harming behavior are important diagnostic criteria of a borderline personality disorder. High level of manifestation of signs of borderline personality disorder is accompanied by such mental states of disadaptation as neurotic depression, asthenia, tension and anxiety.
Keywords: borderline personality disorder; neuroticism; instability of emotions; self-damaging behavior; impulsiveness; anxiety